Republic of Mozambique : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Mozambique's First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Mozambique's performance in 2004 relative to the main macroeconomic objectives of the PRGF-supported program was satisfactory. The fiscal performance through September 2004 was adversely affected by a significant revenue shortfall. The program for 2005 envisages slower growth of 7.3 percent and a further decline in inflation to 8.5 percent by year-end. The program includes additional measures to improve liquidity sterilization, including through the introduction of foreign exchange auctions by end-February 2005.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet